Od konfrontacji do kooperacji – ewolucja postawy ONZ w stosunku do korporacji transnarodowych - Gała, Katarzyna (Historia i Polityka, 2015)
Transnational corporations started to play more and more important role in the international relations, along with accelerating globalization and the growing meaning of the soft, non-military sources of power. The UN made several attempts to regulate transnational business activities by working on appropriate legal solutions. One of them concerned establishing the Code of Conduct for transnational corporations. Gradually, it started to be clear that the differences in the states interests and the opportunities that were offered to corporations by globalization made it difficult to introduce effective mechanisms to limit and control international enterprises. There was a need to change the UN’s attitude towards these actors from confrontation to cooperation, what was reflected by the creation of the Global Compact initiative. In this article there is analyzed the evolution of the UN’s approach to transnational corporations – its genesis, course, and results.